Structurally triggered metal-insulator transition in rare-earth nickelates - Alain Mercy (Nature Portfolio, 2017)
Applications of rare-earth nickelates are hampered by lack of global understanding of the interplay among various degrees of freedom. Here, Mercy et al. propose that the metal-insulator transition of nickelates arises from the softening of an oxygen breathing distortion, providing a united picture of electronic, structural and magnetic properties.